2019
DOI: 10.1039/c8fo02599a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gut microbiota by chlorogenic acid pretreatment on rats with adrenocorticotropic hormone induced depression-like behavior

Abstract: Gut microbiota dysbiosis has been implicated as a vital element in the development or exacerbation of mental disorders, such as major depressive disorder (MDD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 51 publications
1
44
1
Order By: Relevance
“…According to statistics from the World Health Organization in 2015, the incidence rate of depression exceeded 18%, and the disability rate was higher than that for any other disease (Winter et al, 2018). Depression is characterized by disorders of the neurotransmitter, neuroimmunity, neuroendocrine and metabolic systems; however, the pathogenesis of depression is still unclear (Zhang et al, 2015;Ma et al, 2016;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics from the World Health Organization in 2015, the incidence rate of depression exceeded 18%, and the disability rate was higher than that for any other disease (Winter et al, 2018). Depression is characterized by disorders of the neurotransmitter, neuroimmunity, neuroendocrine and metabolic systems; however, the pathogenesis of depression is still unclear (Zhang et al, 2015;Ma et al, 2016;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in these metabolites on concentration may relate to the distinct perturbation of the composition of gut microbiota in induced depression rats, such as Bacteroides, Clostridium, Coprococcus, Pseudobutyrivibrio and Dorea genus, which could change the alteration of gastrointestinal motility. 21,51 Furthermore, previous studies have claimed that some chemical components of ZZCD, such as daidzein, genistein, chlorogenic acid, p-coumaric acid, geniposide, caffeic acid, daidzin, and dihydrodaidzein, could modulate the gut microbiota composition, 7,10,24,50,52 while the change in the composition of gut microbiota can inuence the functioning of the hypothalamic-pituitary-adrenal (HPA) and immune system and thus, it may play a crucial role in depression through the brain-gut axis. 21,22,51 The ZZCD-related chemical components, whose concentration changed signicantly in feces of normal and depression rats, including excreted components and the residual components from the initial ingested decoction, may be responsible for the antidepressant effects of ZZCD in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the correlation among the chemical components of ZZCD, gut microbiota and depression, it is signicant to reveal the pharmacodynamic material basis of ZZCD for studying its metabolic in feces of normal and depression rats. 7,[21][22][23][24] In view of the interference of a great variety of compounds and microorganisms in feces of a living organism, it is difficult to study the analytes of interest. [25][26][27] For avoiding the metabolism of the microorganisms present in the rat feces samples from affecting the composition of the sample under study, multiple analytical strategies were adopted in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al. (2019) reported that 5‐CQA (500 mg/kg b.w./day) increased key antidepressant‐related genera Burkholderiales and Bifidobacterium ; and decreased prodepression Desulfovibrionales, Desulfovibrio , and Klebsiella populations, in adrenocorticotropic hormone‐treated rats. When translated to a 70 kg human at 35 g of 5‐CQA per day, this dose level is nearly unreported in a normal human diet, therefore, the results might find more value in clinical and medicinal applications.…”
Section: Effect Of Hca On Gut Microbiota and Functionmentioning
confidence: 99%